Evaluation of the Success of Vaginal Birth After Cesarean Section Among Patients Attending the Maternity Department at Al-Zawiya Medical Center - Ghadda Mohamed; Naamat Abid; Marwah Bayoudh; Shayyima Jummah; Mohamed Alastay (Khalij-Libya Journal of Dental and Medical Research, 2025)
This study provides compelling evidence that VBAC represents a safe and increasingly successful option for appropriately selected women. The identification of maternal age and neonatal weight as key predictive factors allows for more precise patient counseling and clinical decision-making. The demonstrated improvement in VBAC rates over a single year suggests that with proper protocols, training, and institutional support, healthcare systems can safely increase VBAC utilization while reducing unnecessary repeat cesareans. These findings should encourage healthcare providers to thoughtfully consider VBAC as a viable option for eligible patients, while maintaining rigorous safety standards and individualized care approaches. Continued research and quality improvement initiatives will further refine our understanding and management of VBAC in contemporary obstetric practice.